Concepts, models and measurement of continuity of care in mental health services: A systematic appraisal of the literature. Issue 6 (August 2017) - Weaver, N.; Coffey, M.; Hewitt, J.
Accessible summary: What is known on the subject?: Care continuity is considered to be a cornerstone of modern mental health care. As community mental health services have become increasingly fragmented and complex, the crucial criterion for best quality care has become the degree to which treatment delivered by separate services and professionals is continuous and well coordinated. However, clarification of the key elements of continuity has proved challenging and a consensus has not been reached. Recent research has shown significant levels of variation in the quality of care coordination across England and Wales, with potentially detrimental consequences for individuals. What this paper adds to existing knowledge?: Studies on care continuity identified in this review are grouped into three categories: studies defining concepts of care continuity, studies providing models of continuity and studies describing development of questionnaires about care continuity. There are many similarities and parallels between concepts of continuity described in the studies under review. Therefore, there is potential for developing a consensus on the nature of care continuity as a multidimensional concept. The priority placed upon the patient's experience of care continuity is identified as a major focus in these studies. What are the implications for practice?: A consensus on the nature of care continuity would benefit both theory and practice in mental health nursing. It would provide a firmer foundation for new research seeking to improve continuity for people using services, and enable mental health nurses working as care coordinators to have a better understanding of the elements of their role that are most effective. Abstract: Introduction: The increased complexity of community mental health services, and associated fragmentation of traditional dividing lines between services, has underscored the centrality of care continuity and coordination in modern mental health care. However, clarification of the key features of the care continuity concept has proved difficult and a consensus has not been reached. Aim/Question: This review draws together and critically examines latest evidence concerning concepts, models and scales based on a multidimensional understanding of care continuity. Method: Databases ASSIA, PubMed, MEDLINE and Cochrane were searched for papers dating from January 2005 to July 2016, of which 21 articles met the inclusion criteria. These were subjected to quality appraisal based on CASP and COSMIN checklists. Studies were grouped into three thematic categories describing concepts, models and scales of care continuity. Results/Discussion: Synthesis indicated correspondence between independent, multidimensional models of care continuity, providing greater clarity regarding the essential features of the concept. Association, although not causation, between care continuity factors and health outcomes is supported by current evidence. Implications for practice: Clarification of care continuity in mental health services may enable nurses working as care coordinators to develop a better understanding of key elements of their role, and provide guidance for future service development.